The impact of a giant: A spatial analysis of the fate of our neighbourhood sundry shops - Majid, M. Rafee; Yaakup, Yuhanis (2008)

(untitled)
Kedai runcit or sundry shops have been a standard feature of our housing estate landscape ever since there were housing estates. These mom-and-pop operations have been selling to their surrounding residents everyday essentials such as groceries, fresh produce, poultry, toiletries, etc. Their reasonable price and close distance have made them popular among residents of the housing estates in which they are located. Lately, though, their popularity has been on the decline due to competition from wholesale markets or hypermarkets which can offer the same items cheaper and conveniently under one roof. Local and foreign-bred hypermarkets such as Giants, Tesco and Carrefour have been invading our towns, big and small, leaving the traditional sundry shops fighting for their business. Many of these small-scale individually-owned shops have since closed their operations permanently or moved them a little further outskirt of town, away from the hypermarket catchment. Just how serious is the impact of these hypermarkets on the operation of the sundry shops has so far not been fully investigated in Malaysia although many studies have been carried out elsewhere. Thus, this paper presents a study that has been carried out by the authors to investigate how serious the impact is in Johor Bahru. A sample of three hypermarkets was chosen for this study. Using GIS, we spatially showed the annual changes in the density of sundry shop licenses issued by the local authority within the catchment of each hypermarket, three years before as well as three years after the inaugural date of the hypermarket. Also using GIS, we corroborated the decline in the number of sundry shops within the surrounding housing estates with the residing addresses of the surveyed customers of the hypermarkets. The results obtained confirmed that the operation of hypermarkets does contribute to the decline in the number of sundry shops and the degree of the decline decreases radially outward from the location of the hypermarkets. The findings from this study suggest that some rethinking needs to be done about the manner in which hypermarket licenses, or sundry shop licenses for that matter, are issued. Even our current policy of allowing a certain percentage of new housing development to be set aside for shoplots may also need to be reviewed.